As vozes do sul: uma análise da participação social e cidadã a partir do trabalho do parlamento do Mercosul e da cúpula social do Mercosul - Monteiro, Michelle Alves (Universidade do Vale do Rio dos Sinos, 2021)
MERCOSUR completed 30 years of existence on March 26 of this year, 2021, and with that, the Citizenship Statute was released. This document brings together all the rights that the States Parties understand to constitute the citizenship of Mercosur, including political rights. Located in a region marked by coloniality and democratic fragility, MERCOSUR strategically positions itself as an integration process, what strengthens its consolidation, but also makes it dependent of regional democracy for its effectiveness. The debate about citizenship as a basic element of democracy permeates political participation. In this sense, several participatory mechanisms were created in order to foment the democratic character of the regional integration initiative, including the MERCOSUR Parliament, in regard to representation, and the MERCOSUR Social Summits, understood as an instrument for participatory democracy. Based on this scenario and with the general objective of confirming that social participation in MERCOSUR is related to the elaboration of regional citizenship, the following research problem is noted: to what extent does PARLASUL and the MERCOSUR Social Summit present themselves as tools for consolidating the active participation of civil society into building a regional citizenship in MERCOSUR? As a final result, even with difficulties regarding legitimacy, institutionality and social control and transparency, such political forums can be considered consolidating the democratic participation of the civil society as well as building regional citizenship based on a multidimensional perspective of integration, through its improvement and strengthening, thus, confirming the hypothesis presented. Therefore, in order to answer the problem and prove the aforementioned hypothesis, the inductive approach is used, as well as the historical, normativedescriptive, comparative and empirical procedures. Moreover, through the literary review, document analysis and semi-structured interviews research techniques, the understanding of the construction of citizenship and the consolidation of democracy based on initiatives for social and citizen participation in MERCOSUR is intended.

El MERCOSUR cumplió 30 años de existencia el 26 de marzo de este año 2021, y con ello fue publicado el Estatuto de la Ciudadanía, documento que reúne todos los derechos que los Estados Partes entienden como constituyentes de la ciudadanía del MERCOSUR, incluido el derecho político. Ubicado en una región marcada por la colonialidad y la fragilidad democrática, el MERCOSUR se posiciona estratégicamente como un proceso de integración que se fortalece, al mismo tiempo que depende de la democracia regional para su efectiva consolidación. El debate sobre la ciudadanía como elemento básico de la democracia impregna la participación política. En este sentido, se crearon varios mecanismos participativos con el fin de impulsar el carácter democrático de la iniciativa de integración regional, entre ellos, el Parlamento del MERCOSUR, en el ámbito de la representación, y las Cumbres Sociales del MERCOSUR, entendidos como instrumentos de democracia participativa. A partir de este escenario y con el objetivo general de demostrar que la participación social en el MERCOSUR está relacionada con la elaboración de la ciudadanía regional, se evidencia como problema de investigación el siguiente: ¿en qué medida el PARLASUR y la Cumbre Social del MERCOSUR se presentan como herramientas para consolidar la participación activa de la sociedad civil en el proceso de construcción de ciudadanía regional en el MERCOSUR? Como resultado final, se confirma la hipótesis de que, aun con dificultades de legitimidad, institucionalidad, control social y transparencia, dichos foros políticos pueden considerarse capaces, dada una perspectiva multidimensional de integración, de consolidar la participación democrática de la sociedad civil, así como la construcción de la ciudadanía regional, a través de su mejora y fortalecimiento. Así, para dar respuesta al problema formulado y confirmar la hipótesis señalada, se utiliza el enfoque inductivo, así como los métodos de procedimiento histórico, normativo-descriptivo, comparativo y empírico. Para ello, se utilizan técnicas de investigación como la revisión de la literatura, el análisis de documentos y la realización de entrevistas semiestructuradas para comprender la construcción de ciudadanía y la consolidación de la democracia a partir de iniciativas de participación social y ciudadana en el MERCOSUR.
Keywords: Mercosul; Democracia; Participação social e cidadã; Parlasul; Cúpula social do Mercosul; Mercosur; Democracy; Social and citizen participation; Mercosur social summit; Participación social y ciudadana; Parlasur; Cumbre social del Mercosur; ACCNPQ::Ciências Sociais Aplicadas::Direito